Nanocellulose-Based Biomedical Scaffolds in Future Bioeconomy: A Techno-Legal Assessment of the State-of-the-Art - Mishra, Pawan Kumar; Pavelek, Ondrej; Rasticova, Martina; Mishra, Harshita; Ekielski, Adam (Frontiers in Bioengineering and Biotechnology, 2022)
Nanocellulose is a broader term used for nano-scaled cellulosic crystal and/or fibrils of plant or animal origin. Where bacterial nanocellulose was immediately accepted in biomedicine due to its "cleaner" nature, the plant-based nanocellulose has seen several roadblocks. This manuscript assesses the technological aspects (chemistry of cellulose, nanocellulose producing methods, its purity, and biological properties including toxicity and suggested applications in final drug formulation) along with legal aspects in REACH (Registration, Evaluation, Authorization, and Restriction of Chemicals) regulation by European Union, EMA (European Medicine Agency). The botanical biomass processing methods leading to the nanoscale impurity (lignin and others) on nanocellulose surface, along with surface modification with harsh acid treatments are found to be two major sources of "impurity" in botanical biomass derived nanocellulose. The status of nanocellulose under the light of REACH regulation along with EMA has been covered. The provided information can be directly used by material and biomedical scientists while developing new nanocellulose production strategies as well as formulation design for European markets.